New sequence variants associated with bone mineral density - Styrkarsdottir, Unnur; Halldorsson, Bjarni V; Gretarsdottir, Solveig; Gudbjartsson, Daniel F; Walters, G Bragi; Ingvarsson, Thorvaldur; Jonsdottir, Thorbjorg; Saemundsdottir, Jona; Snorradóttir, Steinunn; Center, Jacqueline R; Nguyen, Tuan V; Alexandersen, Peter; et al. (Nature genetics, 2009)
Unnur Styrkarsdottir and Kari Stefansson and colleagues report the results of an expanded genome-wide association study for bone mineral density at the hip or the spine. New SNP associations were identified downstream of the SOST gene on 17q21, and in intron 1 of the MARK3 gene on 14q32. In an extended genome-wide association study of bone mineral density among 6,865 Icelanders and a follow-up in 8,510 subjects of European descent, we identified four new genome-wide significant loci. These are near the SOST gene at 17q21, the MARK3 gene at 14q32, the SP7 gene at 12q13 and the TNFRSF11A ( RANK ) gene at 18q21. Furthermore, nonsynonymous SNPs in the C17orf53, LRP4, ADAM19 and IBSP genes were suggestively associated with bone density.